Treadmill Slope Modulates Inflammation, Fiber Type Composition, Androgen, and Glucocorticoid Receptors in the Skeletal Muscle of Overtrained Mice - da Rocha, Alisson L.; Pereira, Bruno C.; Teixeira, Giovana R.; Pinto, Ana P.; Frantz, Fabiani G.; Elias, Lucila L. K.; Lira, Fábio S.; Pauli, José R.; Cintra, Dennys E.; Ropelle, Eduardo R.; de Moura, Leandro P.; Mekary, Rania A.; et al. (Frontiers in Immunology, 2017)
Overtraining (OT) may be defined as an imbalance between excessive training and adequate recovery period. Recently, a downhill running-based overtraining (OTR/down) protocol induced the nonfunctional overreaching (NFOR) state, which is defined as a performance decrement that may be associated with psychological and hormonal disruptions, and promoted intramuscular and systemic inflammation. To discriminate the eccentric contraction effects on IL-1beta, IL-6, IL-10, IL-15 and SOCS-3, we compared the release of these cytokines in OTR/down with other two overtraining (OT) protocols with the same external load (i.e., the product between training intensity and volume), but performed in uphill (OTR/up) and without inclination (OTR). Also, we evaluated the effects of these OT models on the muscle morphology and fiber type composition, serum levels of fatigue markers and corticosterone, as well as androgen (AR) and glucocorticoid (GR) expressions. For EDL, OTR/down and OTR groups increased the cytokines and exhibited micro-injuries with polymorphonuclear infiltration. While OTR/down group increased the cytokines in soleus muscle, OTR/up group only increased IL-6. All OT groups presented micro-injuries with polymorphonuclear infiltration. In serum, while OTR/down and OTR/up protocols increased IL-1beta, IL-6 and TNF-alpha, OTR group increased IL-1beta, IL-6, IL-15, and corticosterone. The type II fibers in EDL and soleus, total and phosphorylated AR levels in soleus, and total GR levels in EDL and soleus were differentially modulated by the OT protocols. In summary, the proinflammatory cytokines were more sensitive for OTR/down than for OTR/up and OTR. Also, the specific treadmill inclination of each OT model influenced most of the other evaluated parameters.